The comparative empirical analysis of the social protection system in selected Central and Eastern European countries: Emerging models of capitalism - Piotr Maszczyk (International Journal of Management and Economics, 2020)
This article analyzes the institutional architecture and the level of similarity between the social protection system in 11 new EU member states from Central and Eastern Europe and chosen Western European countries, representing four different models of capitalism identified by Amable. In the selected institutional area, a comparative analysis was performed, and based on it, similarity hexagons were created. They serve the purpose of comparing Central and Eastern European (CEE) countries with Western European countries of reference. The dynamic approach adopted in this study-two different time periods were compared-allows an analysis of path dependence and the evolution of institutional architecture over time. The analysis indicates that in 2014, in the area of social protection, almost all CEE countries, apart from Latvia and Romania, were most comparable to the Continental model of capitalism represented by Germany. Nevertheless, the variety of results for the individual variables (especially input and output variables) and substantial changes between 2005 and 2014 also show that the model of capitalism prevailing in Central and Eastern Europe in the area of the social protection system is evolving constantly at a very fast pace and thus currently may be called a hybrid or even patchwork capitalism.
Keywords: P51; 650; varieties of capitalism; institutions; CEE countries; post-communist capitalism